Ironia w felietonach Jerzego Urbana (tygodnik „Nie” 2004) - Paroń, Katarzyna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
The article analyzes the usage of irony and self-irony found in chosen columns written by Jerzy Urban, published in the weekly magazine “NIE” in 2004. The author uses a classical classification of irony types, concentrating particularly on the most common, namely asteism and mycterism. The author also considers other irony classifications, notably that of D. Sperber and D. Wilson, and employs the concept of irony of D.S. Muecke. The irony in Jerzy Urban’s texts serves as a base for creativity, as well as a method for perceiving reality. We can treat it as a lead, a rhetorical figure, mocking play or word play between the thesis and the conclusion. Irony thus constructed combines artistry with the perception of reality. It is not just an attitude towards life – it is a method of living.